A Bibliometric Analysis of Email Marketing - Loso Judijanto; Rini Fitrianingrum (Westscience Press, 2026)
In this study, we conduct the bibliometric analysis of email marketing research in order to examine its intellectual structure, theme development, and patterns of global collaboration. The database for data collection is a scientific database while the methods of bibliometric analysis include co-occurrence, co-authorship, co-citation analysis, and visualization with the help of VOSviewer software. The results indicate that email marketing research is firmly rooted in the field of marketing as there are prevailing keywords like “marketing,” “electronic mail,” “digital marketing,” and “social media.” In terms of themes, the research stream can be divided into four streams: strategic digital marketing and e-commerce performance, consumer behavior and communication channels, technology and computational methods which include machine learning and artificial intelligence, as well as security issues like spam and phishing detection. As for temporal trends, the research moved from the basic research on the internet to the data driven and personalized marketing. The collaboration analysis identifies a fragmented but nevertheless connected global research network with USA and India being the centers of international collaboration.